ナンキョク ノ チキュウ カガク テキ チネツ タンサ ドライバレー バンダコ シュウヘン ヨホウ - 古賀, 昭人; コガ, アキト; KOGA, Akito (国立極地研究所, 1977)
P(論文) ドライバレー,バンダ湖周辺の地球化学的地熱探査の一手段として,水銀をイソディケーターとする方法が適用できるかどうかの予備調査が行われた.試料は堆積物やコアーサソプルの23個で,平均値は50 ppbであった.対象として,ドンファンDVDP 5Aの14個,テイラー谷DVDP 11の27個,昭和基地周辺の48個がなされたが,それぞれの水銀含有量の平均値は6,12,10 ppbでバンダ湖周辺に特別に水銀が多いことが確認された.水銀は現在地熱探査の最良のインディケーターであり,南極のような酷寒地でも深部に地熱があれば水銀が上昇することは容易に考えられる.これらの事は,バンダ湖周辺の二次生成鉱物中に熱水起源のものがあるという事実の裏付けである.本予備調査は既存の試料についてなされたが,地熱探査用の試料採取により,もっと判然とすると思われる. Preliminary geochemical prospecting of thermal sources around Lake Vanda, Dry Valley, was carried out using mercury. Twentythree samples, taken from around the lake, were analyzed. Values range from 1.1 to 169 ppb, with 50 ppb average. For comparison, 89 samples from Don Juan DVDP 5A, Taylor Valley DVDP 11 and around Syowa Station were also analyzed, obtaining the average values 6, 12, 10 ppb, respectively. Mercury measurements in soil, clay and rock samples would be a new technique which can be used to locate areas of geothermal activity, even in an extremely cold region such as Antarctica. Mercury values are usually proportional to the underground temperature in a geothermal area. Thus, the Lake Vanda area with rather high mercury contents would suggest the existence of a thermal source under the ground, strongly supporting the occurrence of some hydrothermal minerals around the lake. It is, however, still uncertain whether the heat supply has continued up to date or not. In order to gain further information on geothermal sources around Lake Vanda, more detailed murcury survey would be required. departmental bulletin paper